Recent advances in elaborate interface regulation of BiVO4 photoanode for photoelectrochemical water splitting - Liming Wang; Yaping Zhang; Weibing Li; Lei Wang (Materials Reports: Energy, 2023)
Bismuth vanadate (BiVO4) is an excellent photoanode material for photoelectrochemical (PEC) water splitting system, possessing high theoretical photoelectrocatalytic conversion efficiency. However, the actual PEC activity and stability of BiVO4 are faced with great challenges due to factors such as severe charge recombination and slow water oxidation kinetics at the interface. Therefore, various interface regulation strategies have been adopted to optimize the BiVO4 photoanode. This review provides an in-depth analysis for the mechanism of interface regulation strategies from the perspective of factors affecting the PEC performance of BiVO4 photoanodes. These interface regulation strategies improve the PEC performance of BiVO4 photoanode by promoting charge separation and transfer, accelerating interfacial reaction kinetics, and enhancing stability. The research on the interface regulation strategies of BiVO4 photoanode is of great significance for promoting the development of PEC water splitting technology. At the same time, it also has inspiration for providing new ideas and methods for designing and preparing efficient and stable catalytic materials.